Aspek-aspek Hukum Alih Teknologi dalam Meningkatkan Daya Saing Produksi Teknologi Pertambangan di Indonesia - Sri Wartini (Jurnal Hukum IUS QUIA IUSTUM, 2002)
These writings try to discuss the international and national law aspects in developing the competitive power on mining technology production in Indonesia including the gaps appear between the law aspect of technological transfer nationally and and internationally as well. Besides- that, it discusses about the kinds of technology look like which it could develop the competitive power ofmining technological product in Indonesia.